BIBLIOMETRIC ANALYSIS OF DIGITAL ACCOUNTING USING R BIBLIOSHINY - Irman Firmansyah; Wildan Dwi Dermawan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
Digital technology significantly affects business processes, one of which is the accounting aspect that supports providing fast and accurate financial reports. The use of digital technology in accounting is often called digital accounting. This has prompted researchers to examine the impact of digital technology on accounting. Therefore, many publications have been detected examining this issue but have not mapped it well. This study aims to map research on digital accounting. This research was conducted on the dimensions.ai database from 2013 to mid-2022. Using the keyword â€œdigital accountingâ€, 1,397 documents were obtained consisting of journal articles, book chapters, monographs, preprints, and proceedings. The R biblioshiny software found that the most relevant journals were Contributions to Management Science, IOP Conference Series Material Science and Engineering, and Plos One. Meanwhile, the one with the biggest impact is Plos One. In addition, the most relevant authors are Muravskyi and Shao. But the ones who had the biggest impact were Agrell, Karlsson, and Troshani. The distribution of words is dominated by â€˜digital transformationâ€™, â€˜accounting informationâ€™, â€˜digital technologiesâ€™, and â€˜digital accountingâ€™. Topics that have emerged in recent years are digital transformation, accounting information, digital accounting, blockchain technology, and accounting systems. Even blockchain technology is still emerging in 2022. These findings illustrate the importance of using digital technology in accounting, thus triggering researchers to continue to develop ideas and other significant findings related to digital accounting.